A spatial model of forest area in the middle ages based on historical, archaeological and geographic data: Case study of 13th-century Chełmno Land (North-Central Poland) - Molewski, Paweł (Quaestiones Geographicae, 2022)
The settlement established under German law in Chełmno Land in the 13th century, the resultant changes in the structure of agriculture and land cultivation techniques, and the growing demand on wood as timber, fuel and raw materials for crafts, all combined to contribute to the significant deforestation of the territory. The extent of this deforestation remains conjectural. The purpose in creating a model of forest area in 13th-century Chełmno Land was to attempt to reconstruct it and determine its size and, consequently, to verify hypotheses concerning the scale and the ultimate end of deforestation in the research area. The spatial model is based on published historical and archaeological data relating to selected components of the geographical environment that pertain to the forest area. A retrogressive method combined with Multi-Criterion Evaluation (MCE) was used to build a forest area model. The basic platform for collecting, analysing and visualising spatial data was the geographic information system (GIS). The presented estimates indicate that the forest area of Chełmno Land in the 13th century was larger than had previously been assumed, at about 20–25% of the entire territory.